(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
Forensic medicine is an important part of criminal justice, which the judiciary resort to, with the purpose of deciding on a number of cases. One of the most important of these cases, in which forensic medicine is the basis for determining criminal responsibility or not, is the case of allegation or suspicion of death by murder or unknown reasons that lead to suspicion of murder. This research will address the evidentiary value of the forensic physician’s report, as it is a means of proof or a means of assessing evidence or an auxiliary procedure for the judge. It will also address the authority of the criminal judge in assessing the forensic report and the position of the Jordanian Court of Cassation on that. A number of findings and recommendations emerged, the most important of which is that the Jordanian legislator has set up the reports and medical committees system No. 13 of 2014 and its amendments. This system deals with many medical committees, including the forensic committee. The Jordan legislator has also defined the system of expertise before regular courts for 2018 and its amendments, according to Article 11 / c which states that a forensic physician shall be appointed either from forensic physicians appointed in the Ministry of Health, the Royal Medical Services, official university hospitals, or from those retired among them. I wish the Jordanian legislator will set up a legal system for forensic physicians, which shall be independent of the medical reports and committees system No. 13 of 2014 and its amendments and the expertise system before regular courts of 2018 and its amendments. The proposed system is the Judicial Committee system for forensic physicians, and the reason for this is because the experience of forensic physicians is often the source of the basis for the judge’s ruling, especially in cases of murder for unknown and suspicious reasons.